1999
DOI: 10.1046/j.1365-3040.1999.00456.x
|View full text |Cite
|
Sign up to set email alerts
|

Ammonium can stimulate nitrate and nitrite reductase in the absence of nitrate in Clematis vitalba

Abstract: Nitrogen assimilation was studied in the deciduous+ is assimilated in the absence of any NO 3 -assimilation. These data show that the potential for nitrate assimilation in C. vitalba is induced by a nitrogenous compound in the absence of its substrate and suggest that NO 3 -assimilation in C. vitalba may have a significant role beyond the supply of reduced N for growth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
54
0
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 49 publications
7
54
0
2
Order By: Relevance
“…Foliar nitrogen concentrations were determined, after a microKjeldahl digestion procedure, by a colorometric assay using a flow injection analysis system (Tecator 5042 Detector and 5012 Analyser, Tecator, UK) as described in Bungard et al (1999).…”
Section: Photosynthetic Gas Exchangementioning
confidence: 99%
“…Foliar nitrogen concentrations were determined, after a microKjeldahl digestion procedure, by a colorometric assay using a flow injection analysis system (Tecator 5042 Detector and 5012 Analyser, Tecator, UK) as described in Bungard et al (1999).…”
Section: Photosynthetic Gas Exchangementioning
confidence: 99%
“…High nitrogen supply favours the conversion of carbohydrates into proteins, which in turn promotes the formation of protoplasm (Arnon, 1972). Nitrogen comprises 7% of total dry matter of plants and is a constituent of many fundamental cell components such as nucleic acids, amino acids, en-zymes, and photosynthetic pigments (Bungard et al, 1999). Ayoub et al(1994) reported that spilt N application had little effect on yield, but decreased lodging and spike population, while grain weight increased.…”
Section: Introductionmentioning
confidence: 99%
“…Leaf samples from 10 seedlings in each treatment were analysed for total phenolics, as described above. Total foliar nitrogen and phosphorous concentrations were also determined, after a Kjeldahl digestion procedure, by a colorimetric assay using a flow injection analysis system (Tecator 5042 detector and 5012 analyser Tecator, UK) as described in Bungard et al (1999).…”
Section: Growth Measurements and Chemical Analysismentioning
confidence: 99%